MOLECULAR GENETIC MARKERS AS PREDICTORS OF TUMOR RESPONSE TO NEOADJUVANT CHEMOTHERAPY FOR RECTAL CANCER - S. R. Altybaev; S. G. Afanasyev; M. V. Zavyalova; I. V. Stepanov; D. A. Sorokin (Сибирский онкологический журнал, 2016)
The review presents the mechanisms involved in the biological behavior of rectal cancer cells. The tumor response to neoadjuvant chemoradiotherapy was evaluated. The characteristics of proliferative activity, apoptosis, cell adhesion, and migration of rectal cancer cells influenced by chemotherapy were described. The relationship between molecular genetic markers and prediction of response to chemoradiation in rectal cancer was shown.